Brainstorming Technique In Teaching Writing Descriptive Text - Febri Anggraini (Channing : Journal of English Language Education and Literature, 2020)
This study investigated the effect of the brainstorming technique to Increase Students’ Writing Skill at the Tenth Grade of MA YPI Darul Huda Lubuk Harjo. The objective of the study was to find and describe whether there any significant difference between students who are taught by using brainstorming techniques and the students who are taught by using the conventional technique to teach writing skills at the tenth grade of MA YPI Darul Huda Lubuk Harjo. Therefore, for this study writer used quasi-experimental design as the method. The population was 158 and for sample 58 students, a sample of this study used purposive sampling. In this study, the writer was collecting the data used a written test as an instrument, and it was analyzed by an Independent t-test using SPSS 16, the result showed that t –obtained was higher than t table (6,573 >2.000), and the value of sig (2 tailed) =0.00 less than the value significance level (0,05). It meant that there were no significant differences between the experimental group and the control group. So, the Alternative Hypothesis (Ha) was accepted and Null Hypothesis was rejected. It can be concluded that Brainstorming Technique was significant to increase students’ writing skills at the tenth grade of MA YPI Darul Huda Lubuk Harjo.